2021
DOI: 10.3390/ijms22168858
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Defects in Niemann–Pick Type C Disease: Mechanisms and Possible Therapeutic Perspectives

Abstract: Niemann–Pick type C (NPC) disease is a wide-spectrum clinical condition classified as a neurovisceral disorder affecting mainly the liver and the brain. It is caused by mutations in one of two genes, NPC1 and NPC2, coding for proteins located in the lysosomes. NPC proteins are deputed to transport cholesterol within lysosomes or between late endosome/lysosome systems and other cellular compartments, such as the endoplasmic reticulum and plasma membrane. The first trait of NPC is the accumulation of unesterifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 119 publications
(136 reference statements)
1
9
0
Order By: Relevance
“…Sphingomyelinase (encoded by SMPD1) breaks down SM into ceramide and phosphocholine. Mutations in SMPD1 cause accumulation of SM in the CNS, leading to dementia, ataxia, and slurred speech as seen in Niemann-Pick disease type A and B [150][151][152] (Fig. 3).…”
Section: Sphingomyelinmentioning
confidence: 99%
“…Sphingomyelinase (encoded by SMPD1) breaks down SM into ceramide and phosphocholine. Mutations in SMPD1 cause accumulation of SM in the CNS, leading to dementia, ataxia, and slurred speech as seen in Niemann-Pick disease type A and B [150][151][152] (Fig. 3).…”
Section: Sphingomyelinmentioning
confidence: 99%
“…Among them, a role could be played by purines, which perform important biological functions at an intracellular level and act extra-cellularly as signal molecules [ 22 ]. Regarding the latter aspect, it has been reported that purines can interfere with the brain mechanisms that ensure proper cholesterol supply to neural cells [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Niemann-Pick disease type C (NPC; OMIM#257220, 607625) is a neurodegenerative multisystem lysosomal storage disorder with an autosomal inheritance pattern caused by impaired intracellular lipid trafficking leading to the progressive accumulation of cholesterol, glycosphingolipids, phospholipids, and sphingomyelin due to pathogenic variants in the NPC1 and NPC2 genes, with 95% of the cases related to variants in the NPC1 gene [ 1 , 2 , 3 , 4 , 5 ]. The storage can happen in a variety of organs and tissues, but the main organs affected are the liver, spleen, lungs, and the central nervous system (CNS) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main clinical features are hepatosplenomegaly, jaundice, fetal hydrops, hypotonia, ataxia, dysphagia, dystonia, and cognitive impairment, among other problems. [ 5 , 7 ] Due to the lysosomal storage of several of these lipids, especially cholesterol in the brain, NPC patients suffer from neurodegeneration due to the massive loss of Purkinje neurons in the cerebellum and diffuse atrophy in other regions, neuroinflammation, and demyelination [ 5 , 8 , 9 ]. The clinical spectrum is thus very heterogeneous, and it can be classified into four main groups based on the age of onset: early infantile, late infantile, juvenile, and adolescent/adult [ 10 , 11 , 12 ]; the lifespan of the patients can range from a few days of life to 60 years of age [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation